Ownership Matters: Not-for-Profit Chain Nursing Homes Have Higher Utilization of Agency Nursing Staff - Rohit Pradhan PhD; Akbar Ghiasi PhD; Gregory Orewa PhD; Shivani Gupta PhD; Ganisher Davlyatov PhD; Bradley Beauvais PhD; Robert Weech-Maldonado PhD (SAGE Publishing, 2024)
Nursing homes (NHs) have long struggled with nurse shortages, leading to a greater reliance on agency nurses. The purpose of this study was to examine the impact of NH ownership on agency nurse utilization. Data were derived from multiple sources, including the Payroll-Based Journal and NH Five-Star Facility Quality Reporting System (n: 38,550 years: 2020-2022). A 2-part logistic regression model with 2-way fixed effects (state and year) was used to assess the association of ownership and agency nurse utilization. Model 1 compared facilities with and without agency nurse use, while Model 2 focused on NHs using agency nurses, examining high utilization (top 10%). The dependent variables were agency nurse utilization ratios for registered nurses (RNs), licensed practical nurses (LPNs), and certified nursing assistants (CNAs). The primary independent variable was ownership/chain affiliation: for-profit chain (FPC), for-profit independent (FPI), not-for-profit chain (NFPC), and not-for-profit independent (NFPI). Model 1 showed that NFPC facilities had higher odds of using agency RNs (OR = 1.65), LPNs (OR = 1.53), and CNAs (OR = 1.38) compared to NFPI facilities (all P  < .001), while FPC facilities also had increased odds for RNs (OR = 1.43), LPNs (OR = 1.30), and CNAs (OR = 1.15) (all P  < .001). Model 2 indicated that NFPC, FPC, and FPI facilities were more likely to be high utilizers (top 10%) of agency nurses, with NFPC facilities having the highest odds across all categories. Pairwise comparisons showed that NFPC had the highest utilization of agency RNs and LPNs compared to other ownership groups. These results highlight the significant impact of NH ownership on staffing practices, suggesting that ownership type influences agency nurse utilization.